Emerging Space Markets - Tkatchova, Stella; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2018)
This book analyzes the commercial space activities and commercialization processes of the last fifteen years and maps the future challenges that NewSpace companies will face developing commercial space markets. What is new and what has happened in these markets up till now? Is there a business case for private companies for commercial space? What are the targeted commercial space markets? Who are the future customers for commercial space transportation markets? How can NewSpace companies attract investors? Can we learn lessons from traditional space industries or other companies in other areas? In what way have the last fifteen years made a difference in the evolution of space markets? Is there a future for in-situ resource mining, space debris services, in-orbit satellite servicing and sub-orbital transportation? What are the lessons learned from ISS commercialization? In addition the reader will find a synopsis of several space transportation programs, commercial space markets, future Moon and Mars missions, in-situ resource exploitation concepts, space debris mitigation projects and sub-orbital commercial markets. Major lessons learned are identified, related to the attraction of first time customers and long term R&D funding, managing technological and market risks and developing new markets and applications.
Commercial Space Markets and Stakeholder -- NASA COTS/ NASA CCDEV and Space Agencies Technology Roadmaps in the context of Commercial Space Markets -- Technology Roadmaps of Newspace companies -- European and International Commercial Space Markets -- Commercial Space Markets and Traditional Space Industry -- Historic Commercialization Lessons Learnt -- Commercial Space Markets Evolution and Challenges -- Financing Commercial Space Projects, developing business cases, strategic, market and technology innovation risks -- Public Private Partnerships (PPP), Joint Ventures and Research Partnerships -- NASA COTS/NASA CCDev Benefits Definition and Impact -- Technology Spin-off, Spin-In and Space Applications.
Keywords: Aerospace engineering; Astronautics; Technological innovations; Solar system; Aerospace Technology and Astronautics; Innovation and Technology Management; Space Physics